Post‐Last Glacial Maximum evolution of a "fjord‐type" lake based on high‐resolution seismic data: the Lago Roca/Acigami (southern Tierra del Fuego, Argentina/Chile). (23rd December 2019) - Bran, Donaldo Mauricio; Lozano, Jorge Gabriel; Civile, Dario; Lodolo, Emanuele; Cerredo, María E.; Tassone, Alejandro; Baradello, Luca; Grossi, Maurizio; Vilas, Juan
ABSTRACT: Lago Roca/Acigami is a "fjord‐type" lake located in the southernmost part of South America, in the proximity of the Beagle Channel. A high‐resolution seismic survey was carried out to analyse the seismic stratigraphy of the lake and to shed some light on the post‐Last Glacial Maximum history of the area. Six seismic units were recognised, and their nature and depositional context were interpreted using seismic stratigraphy and acoustic facies analysis. A buried large ridge was identified within the glacial unit (SU1), interpreted as a frontal moraine that indicates a stabilisation phase. After retreat of the glacier from the basin, the trough was flooded by meltwater and a lake developed (SU2). The seismic facies, from bottom to top, depict a transition from ice‐contact (SU2; SU3) to ice‐distal proglacial conditions (SU4). A thick draping unit (SU5) marks a marine transgressive event and the instauration of a fjord environment in the basin. The marine transgression was a rapid event preceded by a fall in the lake level that caused an erosional unconformity. During the fjord phase the sedimentation remained controlled by meltwater discharge. Sea level fall, and subsequent disconnection from the Beagle Channel was accompanied by a progradation of the glaciofluvial deltaic sediments and the occurrence of several mass‐wasting deposits (SU6). © 2019 John Wiley & Sons, Ltd.